2016
DOI: 10.1093/ckj/sfv147
|View full text |Cite
|
Sign up to set email alerts
|

Post-infectious glomerulonephritis with crescents in adults: a retrospective study

Abstract: BackgroundCrescent formation generally reflects severe glomerular injury. There is sparse literature on post-infectious glomerulonephritis (PIGN) with crescents in adults. This retrospective study looked at nine such cases to see if there is a correlation between the severity of presentation, steroid treatment, histological severity and outcome.MethodsBiopsy reports of all the adults who underwent kidney biopsy from February 2010 to June 2014 in a tertiary care hospital were screened and all the cases with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…6 Similar conclusions were drawn from an older study with a similar-sized cohort ( n = 52). 7 Nevertheless, multiple case reports 4 , 8 , 9 and some observational data 3 do suggest a potential benefit from steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Similar conclusions were drawn from an older study with a similar-sized cohort ( n = 52). 7 Nevertheless, multiple case reports 4 , 8 , 9 and some observational data 3 do suggest a potential benefit from steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data on the role of steroids have been scarce and observational. 2 , 3 , 4 In this study, we report the results of a randomized controlled trial that studied the effect of steroid therapy on renal outcomes in adults presenting with IRGN and a decreased estimated glomerular filtration rate.…”
mentioning
confidence: 99%
“…There is conflicting evidence supporting the use of steroids. Some studies showed good response, but in some studies, no correlation was found between the steroid use and outcome [6, 7, 8, 9]. Here, we report a case of an elderly diabetic male who developed PIGN with crescents after acute gastroenteritis and responded very well to steroids.…”
Section: Introductionmentioning
confidence: 77%
“…Crescentic glomerulonephritis having an underlying immune complex proliferative glomerulonephritis is less responsive to aggressive immunosuppressive therapy as compared to anti-glomerular basement membrane or antineutrophil cytoplasmic antibody crescentic glomerulonephritis but for the minority of patients who have idiopathic immune complex crescentic glomerulonephritis, the most common treatment is immunosuppressive therapy with pulse methylprednisolone, followed by prednisone at a dosage of 1 mg/kg daily tapered over the second to third month to an alternate-day regimen until completely discontinued [13]. Baikunje et al [9] studied PIGN with crescents in adults and observed that those patients who were treated with steroids had excellent response, but the duration of therapy was variable. Our patient initially was on hemodialysis but after 2 weeks of steroid therapy hemodialysis was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…The use of immunosuppressive therapy in PSGN has been controversial [ 3 , 8 ]. Several studies have suggested the benefit of steroids in selected patients, but the exact mechanism is not clear [ 9 - 10 ]. The current expert consensus is to use steroids in patients with more than 30% crescents formation on renal biopsy.…”
Section: Discussionmentioning
confidence: 99%